Ser de ferro: análise da saúde e panorama de trabalho dos motoristas profissionais de caminhão da mineração - Geraldo Fabiano de Souza Moraes (2014)
Introduction: The mining industry occupies an important role in socio-economic and environmental context involving a multitude of impacts. Among the many health risks to workers, there is exposure to whole-body vibration (WBV) in driving trucks for ore transportation. The VCI exposure is associated with health problems, especially for diseases that involve the spine, as in the lower back. Objectives: The aim of this prevalence study was to analyze the health and work conditions of professional drivers mining truck (PDMT) and investigate the relationship between these conditions and the occurrence of low back pain. Methods: The study was conducted in two open pit mines of iron ore mining region of the state of Minas Gerais, Brazil. A questionnaire survey and socio-demographic aspects related to work and health conditions were administered to 128 MPCM. Also it was analyzed aspects related to the current job. The WBV was evaluated according to ISO-2631-1997 standard. Significant variables and the values of the odds ratios (OR) for the occurrence of low back pain reported were determined by applying the logistic regression analysis. Results: It was observed that working conditions are adverse in relation to various aspects of exposure to the environment and the production system organization. The nature of the driver's job requires him to take an extended static posture. The multivariate analysis showed the following significant variables: body mass index [OR = 1.19; CI (95%): 1.06 to 1.35]; high level of education [OR = 0.25; CI (95%): from 0.10 to 0.62]; not use alcohol [OR = 0.45; CI (95%): 0.19 to 1.07]; acceleration equivalent to an eight hours [A (8) x; OR = 1.07; CI (95%): 1.02 to 1.12]; and regular physical activity [OR = 4.54; CI (95%): 1.51 to 13.66]. Conclusions: This study was able to demonstrate the relevance of the risks under the conditions and PDMT work environment, in particular on exposure to the WBV. Variables were identified for the generation of low back pain, results that can contribute to the direction of harm prevention measures in this population of workers.